2008
DOI: 10.1073/pnas.0806037105
|View full text |Cite
|
Sign up to set email alerts
|

GABA A transmission is a critical step in the process of triggering homeostatic increases in quantal amplitude

Abstract: When activity levels are altered over days, a network of cells is capable of recognizing this perturbation and triggering several distinct compensatory changes that should help to recover and maintain the original activity levels homeostatically. One feature commonly observed after activity blockade has been a compensatory increase in excitatory quantal amplitude. The sensing machinery that detects altered activity levels is a central focus of the field currently, but thus far it has been elusive. The vast maj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
62
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(72 citation statements)
references
References 51 publications
7
62
1
Order By: Relevance
“…This recovery of activity occurred before compensatory increases in quantal amplitude were observed, as described previously (Fig. 1A) (17). To determine whether cellular excitability contributed to the recovery of embryonic activity after GABA A receptor blockade, we treated embryos in ovo for either 12 h (E9.5-E10) or 48 h (E8-E10) with saline, the GABA A receptor antagonist gabazine, or the glutamate receptor antagonists 6-cyano-7-nitroquinoxaline-2,3-dione disodium (CNQX) and DL-2-amino-5-phosphonopentanoic acid (APV).…”
Section: Gabaa Receptor Block Increases Intrinsic Excitabilitysupporting
confidence: 80%
See 2 more Smart Citations
“…This recovery of activity occurred before compensatory increases in quantal amplitude were observed, as described previously (Fig. 1A) (17). To determine whether cellular excitability contributed to the recovery of embryonic activity after GABA A receptor blockade, we treated embryos in ovo for either 12 h (E9.5-E10) or 48 h (E8-E10) with saline, the GABA A receptor antagonist gabazine, or the glutamate receptor antagonists 6-cyano-7-nitroquinoxaline-2,3-dione disodium (CNQX) and DL-2-amino-5-phosphonopentanoic acid (APV).…”
Section: Gabaa Receptor Block Increases Intrinsic Excitabilitysupporting
confidence: 80%
“…We have further shown that the compensatory changes in quantal amplitude were triggered through a reduction in GABA A receptor activation (17). In this way, reductions in GABA binding to its receptor signal that network activity levels have been reduced.…”
mentioning
confidence: 63%
See 1 more Smart Citation
“…We may have underestimated the extent of synaptic scaling up as we observed partial reversal of inhibition by CNQX. Nonetheless, Wilhelm and Wenner (2008) used a similar technique of a bolus injection of activity-reducing drugs in the in ovo chick spinal cord and measured the recovery of spontaneous network activity by mechanisms that include synaptic scaling. They showed that injection of a single receptor antagonist such as CNQX resulted in a temporary reduction in spontaneous network activity (as measured by immature limb movements) that recovered to control levels within hours.…”
Section: Behavioral Consequencesmentioning
confidence: 99%
“…From the neural perspective, a wealth of information exists regarding how neurons and circuits maintain target levels of activity despite removing or enhancing activity inputs (termed homeostatic plasticity). However, models to study these processes use pharmacological or pathological paradigms to manipulate neuronal activity in vivo and in vitro primarily at early developmental stages (Hengen et al, 2013;Knogler et al, 2010;Ngodup et al, 2015;Schacher and Hu, 2014;Turrigiano, 2012;Wilhelm and Wenner, 2008). Thus, the bullfrog respiratory control system following overwintering offers a powerful ability to uncover mechanisms leading to and resulting in the preservation (respiratory motor output and hypoxia sensitivity) and deterioration (CO 2 sensitivity) of sensorimotor function in the same species, individual and neural control system after ecologically relevant inactivity.…”
Section: Perspectives and Significancementioning
confidence: 99%